The THD performance of single phase five level inverter using pr and harmonic compensators current controller - Abdullahi, Abdullahi Mohamed (2020)
Iniorderitoimeetitheirequirementifromitheiindustriesidemandiaimediatiaifree-harmonicsiand highipoweriratingisourceiisiremarkablyiincreasediinipastifewiyears.iAsicompareditoisingleleveliinverter,imultileveliinverterioffersiminimumiharmonicidistortioniandihigheripower output. This project is to observe the THD performance of single phase five level inverter using proportional resonant (PR) and harmonic compensators current controller. The PR controller not only solve the current and harmonic problem, but also efficiency and accuracy of equipment in other application. The THD was reduced to 1.6% which is in the scope of the project. More functions were added to the PR current controller to reduce the THD at the 3th, 5th, and 7th, harmonic orders. The THD of the 3th, harmonic order was reduced from 0.45% to 0.1% while the, 5th, and 7th, harmonic orders were reduced from 0.6% and 0.43% to 0.25% and 0.4% respectively. The development and simulation is performed using Matlab/Simulink. The simulation result of experiment is performed by using Fast Fourier Transform analysis (FFT) for the harmonics captured.